Luxembourg : Report on the Observance of Standards and Codes-FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2004)
This report on the Observance of Standards and Codes reviews Luxembourg's observance of the Financial Action Task Force (FATF) 40 Recommendations for Anti-Money Laundering and eight Special Recommendations on Combating the Financing of Terrorism. The assessment reveals that Luxembourg has in place a solid criminal legal framework and supervisory system to address the significant challenge of money laundering. Luxembourg is broadly compliant with almost all of the FATF Recommendations. The main areas requiring further attention relate to the limited scope of predicate offences and the reporting of suspicions of financing of terrorism.